2016
DOI: 10.1016/j.neuroimage.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields of motor and frontal tDCS in a standard brain space: A computer simulation study

Abstract: The electric field produced in the brain is the main physical agent of transcranial direct current stimulation (tDCS). Inter-subject variations in the electric fields may help to explain the variability in the effects of tDCS. Here, we use multiple-subject analysis to study the strength and variability of the group-level electric fields in the standard brain space. Personalized anatomically-accurate models of 62 subjects were constructed from T1- and T2-weighted MRI. The finite-element method was used to compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
145
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 73 publications
11
145
0
Order By: Relevance
“…However, the acute effects are inconsistent across studies (Tanaka et al, 2009, 2011; Montenegro et al, 2015, 2016; Angius et al, 2016; Washabaugh et al, 2016) and seem dependent on tDCS protocols, training tasks, muscle groups, and subject populations. In this context, computational modeling would be useful to understand the different spatial distributions of the electric field induced by different tDCS protocols (electrode configuration, size, or current intensity; Laakso et al, 2015, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the acute effects are inconsistent across studies (Tanaka et al, 2009, 2011; Montenegro et al, 2015, 2016; Angius et al, 2016; Washabaugh et al, 2016) and seem dependent on tDCS protocols, training tasks, muscle groups, and subject populations. In this context, computational modeling would be useful to understand the different spatial distributions of the electric field induced by different tDCS protocols (electrode configuration, size, or current intensity; Laakso et al, 2015, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Twelve subjects per group seem underpowered, although 12 is close to the sample size (15 subjects per group) of Hendy and Kidgell's (2013) study. There is a large inter-individual variation in the outcome of tDCS over the hand motor cortex (Wiethoff et al, 2014; Laakso et al, 2015, 2016), with approximately one-half of subjects failing to respond to the stimulation in the expected manner (Wiethoff et al, 2014). Recently, such a large inter-individual variation was also observed in tDCS over the leg motor cortex (Madhavan et al, 2016; van Asseldonk and Boonstra, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Except for the same scale (ie, mm) SCD and CT had, the vector‐like properties of SCD, including: (a) direction: SCD is a line starting from the point on the scalp and ending at the point on cerebral cortex and (b) magnitude: the measure of SCD representing the length of the line, also have profound impact on the modeling of tDCS. For instance, recent evidence confirmed that the directionality (or orientation) of the current injection can critically influence the field potential of the targeted region during transcranial electrical stimulation . Therefore, region‐specific SCD not only reflects the individual morphometric features, but also provides a useful and dynamic parameter to optimize the therapeutic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The main anatomical component of interest for simulations over midline would be the falx cerebri, a layer of dura roughly 2 mm thick that separates the two hemispheres of the brain (Miga et al, 1999). This area is difficult to segment and thus is not even included in the high resolution MIDA head model (Iacono et al, 2015), although it has been modeled as a discontinuous medium in some studies (Laakso et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…These simulations allowed researchers to look at how both coils and anatomy influence stimulation within individuals, but were limited in their ability to show how stimulation varies between individuals. Recent developments in modeling tools have improved the generation of heterogeneous head models (Windhoff et al, 2013; Thielscher et al, 2015), facilitating the use of several models in studies (Krieg et al, 2015; Lee et al, 2016; Opitz et al, 2013; Laakso et al, 2016a, 2016b; Opitz et al, 2016; Bungert et al, 2016). This is important because the induced E-Field in a single head cannot be representative of the induced E-Field for a population, given the significant differences in head anatomy.…”
Section: Introductionmentioning
confidence: 99%